Critical genealogy of the concept femicide: epistemological, political and feminist debates from Central América and the Caribbean - Mora, Mariana R. (2025)
The following article aims to construct a critical genealogy of the concept of femicide/feminicide. It intends to contribute to the epistemological, political and feminist discussions that have arisen since the end of the 1970s and that continue today to expand this issue. From a situated perspective, I wish to emphasize the pioneering place of Central America and the Caribbean in this debate. This paper is part of the results of a doctoral research that analyzed the tensions for recognition and the struggles for justice around femicides in Costa Rica. Methodologically, it is based on a systematic review of existing academic literature, as well as in-depth interviews with academics on the subject. As part of the conclusions, I insist on the notion of epistemic justice and the necessary recognition of social movements in the production of feminist knowledge.